2018
DOI: 10.32890/mjli2017.14.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Efl Doctoral Students on Challenges of Citations in Academic Writing

Abstract: Purpose-Citation is vital in academic writing but particularly challenging for novice writers who use English as a second or foreign language. While much is known about citations types and functions, scarce knowledge is available about what makes citing a complicated procedure. Hence, this study explores the difficulties in citing and integrating information from academic sources into the literature review chapter of PhD proposals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 47 publications
0
25
0
1
Order By: Relevance
“…Students experience some problems related to publication, such as their limited academic skills and research methods' skills (Bamgboje-Ayodele et al, 2016). Also, Jomaa and Bidin (2017) found that Arab PhD students face challenges in their academic writings because of their limited knowledge of the foreign language. As a result, the low level of proficiency prevents them from making a sufficient discussion in the target language (Al Fadda, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Students experience some problems related to publication, such as their limited academic skills and research methods' skills (Bamgboje-Ayodele et al, 2016). Also, Jomaa and Bidin (2017) found that Arab PhD students face challenges in their academic writings because of their limited knowledge of the foreign language. As a result, the low level of proficiency prevents them from making a sufficient discussion in the target language (Al Fadda, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, English as a Medium of Instruction (EMI) represents a serious challenge for PhD candidates. For example, Jomaa and Bidin (2017), found that Arab PhD students faced challenges in their academic writings because of their limited knowledge of the foreign language. As a result, the low level of proficiency prevents them from making a sufficient discussion in the target language (Al Fadda, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in their study, Mansourizadeh and Ahmad (2011) showed that published articles by expert writers in chemical engineering used Naming more than Verb controlling with 6.97 % and 6.56%, respectively, whereas unpublished papers by novice writers used Verb controlling more than Naming. The discourse-based interviews revealed that EFL students, particularly Vietnamese and Arab postgraduates, were not aware of the rhetorical functions implied in citations and they had linguistic difficulties in implicitly acquiring the conventions of citations (Nguyen & Pramoolsook, 2016;Jomaa & Bidin, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, advanced academic literacy assumes that mastering the disciplinary practices could enhance students' control of the varied cultural and linguistic structures that are essential for them to engage critically with texts (Hyland & Jiang, 2018a) by means of using the metadiscourse markers. The significance of adopting an authorial stance in academic writing has recently received a considerable amount of research (Hyland & Jiang, 2018a, 2018bJiang & Wang, 2018;Jomaa & Bidin, 2017). Therefore, successful writers should be familiarized with using a range of rhetorical features to highlight the novelty of their research, evaluate their findings, and establish harmony with their readers (Hyland & Jiang, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, successful writers should be familiarized with using a range of rhetorical features to highlight the novelty of their research, evaluate their findings, and establish harmony with their readers (Hyland & Jiang, 2018b). However, university students (Donahue, 2004;Morton & Storch, 2018) particularly EFL postgraduates (Jomaa & Bidin, 2017) seem to have difficulties in academic writing (Almatarneh, Rashid, & Yunus, 2018), in adopting a stance and projecting their voice due to having insufficient guidelines on using evaluative expressions and/or being unaware of using metadiscourse markers. Hence, this study explores the use of metadiscourse markers utilizing the Systemic Functional Linguistics approach.…”
Section: Introductionmentioning
confidence: 99%